Pengaruh Model Pembelajaran Snowball Throwing Terhadap Hasil Belajar Siswa Kelas V di SDN Ciptamuda - Na'imah, Syayidatun; Supangat; Dewi, Tri Ratna (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This research was motivated by the fact that on the ground the KKM results for students were still low in almost all subjects, especially in thematic subjects at SDN Ciptamuda because the teachers did not vary in the application of learning models, so the snowball throwing model was offered. The purpose of this study was to improve student learning outcomes in fifth grade Thematic learning at SDN Ciptamuda. This research is an experimental research with a Quasi Experimental Design in the form of One Group Pretest-Postest Design. Data collection was carried out using tests, observation guides and documentation. The results of the study are that the application of the snowball throwing learning model can improve student learning outcomes in thematic learning. The conclusion in this study is that student learning outcomes after using the snowball throwing learning model in the Thematic subject of fifth grade students at Ciptamuda Elementary School have increased. This can be seen from student learning outcomes before being given treatment with an average score of 42.9. However, after being given treatment, student learning outcomes increased by 92.3. Learning completeness before being given Treatment and after being given Treatment had increased from 40% to 90% and the results of teacher and student observations had been carried out well. From these data it can be concluded that there is an influence on student outcomes between before and after being treated using the Snowball Throwing learning model.